Host plant selection by larvae of the muga silk moth, antheraea assamensis, and the role of the antenna and maxillary palp - Bora, Dipsikha S.; Deka, Bhabesh; Sen, Avolikiteswar (Journal of Insect Science, 2013)
The importance of olfactory senses in food preference in fifth instar larvae of Antheraea assamensis Helfer (Lepidoptera: Saturniidae) was examined by subjecting larvae with only antennae or maxillary palpi after microsurgery to food and odor choice tests. Mean percent consumption, total consumption, and choice indices were used as parameters for drawing conclusions. The foods used were two hosts, two non-hosts, and a neutral medium (water). Both antennae and maxillary palpi were fully competent in preference for host plants, Persea bombycina Kostermans (Laurales: Lauraceae) and Litsea polyantha Juss, over the non-hosts, Litsea grandifolia Teschner and Ziziphus jujuba Miller (Rosales: Rhamnaceae). Both were competent in rejecting the non-hosts, L. grandifolia and Z. jujuba. The odor choice test was carried out using a Y-tube olfactometer and showed similar results to the ingestive tests. The results indicate the necessity of functional integration of a combination of olfactory and gustatory sensilla present in different peripheral organs in food acceptance by A. assamensis larvae.
Keywords: food choice; maxillae; Y-tube olfactometer